The teaching of English in public primary schools in Mexico: More heat than light? - Ramírez-Romero, José Luis; Sayer, Peter (Education Policy Analysis Archives, 2016)
The national English program in Mexico was formally launched in 2009. The new program supplanted various state programs, and aimed to create a coherent, uniform curriculum that extended English instruction to all public school students across the country. The article describes the development, evolution, and changes as the program was piloted and implemented. The authors synthesize various sources to identify the accomplishments of the program and the challenges that remain. They argue that a main concern, from a policy perspective, is that the program has not been conceptualized as part of a broader coherent language education policy, and that the program has been implemented not as an education policy, but as a series administrative and fiscal actions. Hence, while the program has succeeded in expanding access to English in public schools, it has not had continuity and has been characterized by inconsistency and change.